Hardware efficient frequency estimator based on data-aided algorithm for digital video broadcasting system - Ryu, C.D.; Park, J.W.; Myung Hoon Sunwoo; Pan Soo Kim; Dae-Ig Chang (APCCAS 2008-2008 IEEE Asia Pacific Conference on Circuits and Systems, 2008)
This paper presents an efficient frequency estimator for digital video broadcasting - second generation (DVB-S2). Analyzing the robust algorithm among data-aided approaches, we find that the Luise & Reggiannini (L&R) algorithm is the most suitable one for coarse frequency estimation with respect to estimation performance and complexity. However, it requires many multipliers and adders to compute output values of correlators. We propose an efficient architecture identifying the serial correlator with the buffer and multiplexers. The proposed coarse frequency estimator can reduce the hardware complexity about 92% of the direct implementation. The proposed architecture has been implemented and verified on the Xilinx Virtex II FPGA.